EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT (TGT) DAN TEAM ASSISTED INDIVIDUALIZATION (TAI) DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI KECERDASAN LOGIS MATEMATIS SISWA KELAS VII SMP NEGERI SE-KABUPATEN KARANGANYAR - Uyun, Musmiratul; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: This research aimed to know: (1) which one of the learning models with scientific approach gave a better mathematics achievement, TGT, TAI, or classical; (2) which one has a better mathematics achievement, the students with high logical mathematical intelligence( LMI), the students with the medium LMI, and the students with the low LMI; (3) in each learning models with scientific approach, which one has a better mathematics achievement, the students with high LMI, the students with the medium LMI, and the students with the low LMI; (4) in each category LMI, which one gave a better mathematics achievement, TGT, TAI, or classical. This research used the quasi experimental research method with the factorial design of 3 x 3. This population was all of the students in Grade VII of State Junior Secondary Schools of Karanganyar. The samples of the research were taken by using the stratified cluster random sampling technique. The instruments used to gather the data were test of learning achievement in mathematics and test of LMI. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research were as follows. 1) The students instructed TGT had a better learning achievement in mathematics than those instructed TAI and those instructed with the classical learning model. Furthermore, the students instructed with TAI had a better learning achievement in mathematics than those instructed with the classical learning models. 2) The learning achievement in mathematics of the students with the high LMI was better than that of the students with the medium LMI and the students with the low LMI. In addition, the learning achievement in mathematics of the students with the medium LMI was better than that of the students with the low LMI. 3) In each learning model of the TGT, TAI, and the classical learning models, the students with the high LMI had a better learning achievement in mathematics than that of   those with the medium LMI and those with the low LMI. Moreover, the students with the medium LMI had a better learning achievement in mathematics than that of those with the low LMI. 4) In each of the students with the high, medium, and low LMI, TGT gave  better learning achievement in mathematics than TAI and the classical learning models. Furthermore, TAI gave better learning achievement in mathematics than the classical learning models.Keywords: Teams Game Tournament (TGT) Team Assisted Individualization (TAI),  learning achievement, mathematical intelligence